1976
DOI: 10.1177/002224377601300307
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Trial and Incentives on Repeat Purchase Behavior

Abstract: Although relatively under-researched, behavioral influence strategies commonly are used by marketers to modify consumer demand. Reported here are the results of a field experiment which tested the effectiveness of trial and incentive behavioral influence strategies. The efficacy of using self-perception theory to explain and predict behavior is assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(44 citation statements)
references
References 37 publications
2
42
0
Order By: Relevance
“…Two recent papers considered promotions from the point of view of self perception theory. Scott (1976) found weak repeat behavior in response to a number of different one-time incentives, although some (a discounted trial) did better than others (free trial, free trial plus premium). From a behavioral learning perspective the results are also weak, but serve as a case to support the notion presented earlier that shaping procedures are generally poorly used.…”
Section: A Review Of Some Promotions Literaturementioning
confidence: 93%
See 1 more Smart Citation
“…Two recent papers considered promotions from the point of view of self perception theory. Scott (1976) found weak repeat behavior in response to a number of different one-time incentives, although some (a discounted trial) did better than others (free trial, free trial plus premium). From a behavioral learning perspective the results are also weak, but serve as a case to support the notion presented earlier that shaping procedures are generally poorly used.…”
Section: A Review Of Some Promotions Literaturementioning
confidence: 93%
“…Poor (Scott 1976)-Free trial did not help Good (Dodson, Tybout, Sternthal 1978), Led to repeat purchase…”
Section: Self Perception Theorymentioning
confidence: 99%
“…Evidence supporting or disputing these theories is scanty. A number of published articles support the observation that people who buy a brand on a deal (not necessarily a coupon) are less likely than people who buy the same brand at the regular price to repurchase the brand once the deal is removed (Guadagni & Little, 1983;Jones & Zufryden 1981;Lawrence, 1969;Scott, 1976). Shoemaker and Shoaf (1977), for instance, analyzed three sequential purchases of households.…”
Section: H4mentioning
confidence: 99%
“…In addition, given the processes proposed in self-perception theory, high-value extrinsic motivators undermine intrinsic motivation to a greater extent than do low-value extrinsic motivators. Two studies have found support for the self-perception theory prediction that the size of the extrinsic motivator influences repeat purchase probabilities (Dodson, Tybout, & Sternthal, 1978;Scott, 1976).…”
Section: Self-perception Theorymentioning
confidence: 99%